Homemade pericardial bifurcated graft for Q fever-infected abdominal aortic aneurysm open repair: a case report - Mouche, A.; Baron, J.; Toquet, C.; Le Corvec, T.; Maurel, B.; Benichou, A.; Mougin, J. (Frontiers in Cardiovascular Medicine, 2024)
Q fever is a zoonotic infection caused by Coxiella burnetii. In rare case, it can lead to vascular complications, including infected aneurysms. Successful treatment involves surgery and antibiotics, but there is no established consensus or clear recommendation for the choice of material graft.We report a case of abdominal aortic aneurysm infected by Coxiella burnetii treated by open surgery with complete resection of the aneurysm and homemade bovine pericardial bifurcated graft reconstruction and long term antibiotherapy by Doxycycline.One year after the surgery, the patient had no sign of persistent infection or vascular complication. Moreover, C. burnetii immunoglobulins titers decreased after 6 months postoperative.